The Relationship Of Learning Interest And Historical Awareness With Students Learning Outcomes In History Subjects - Nusa Peninda Hakim; Muhammad Fakhruddin; Abrar Abrar (Amal Insani Foundation, 2024)
This research aims to determine the relationship between interest in learning and historical awareness on the learning outcomes of class XI students at SMK Negeri 4 Jakarta. This research was conducted from April to May 2024. The research method used was ex-post facto research. The research results are as follows. 1) There is a significant positive relationship between interest in learning and student learning outcomes. 2) There is a significant positive relationship between historical awareness and student learning outcomes. 3) There is a significant positive relationship between interest in learning and historical awareness and student learning outcomes. Thus, the results of this research can be concluded that there is a significant positive relationship between interest in learning and historical awareness and student learning outcomes